A justiça em Platão e a filosofia do direito - Gonzaga, Alvaro Luiz Travassos de Azevedo (2007)
The present work intends to study the change in the platonic doctrine from the Young Dialogues to the Average Dialogues, concerning the Theory of the Cardinal Virtues (Justice, Moderation, Courage and Wisdom). We will analyze the unicity of the Virtues in Protagoras, as well as the possibility of their dissociation in The Republic. Still in The Republic, we shall explore how Justice is constructed in the idealistic platonic city. Finally, we will approach the possibility of the conflict between the soul and the acrasia